Examining Sleep and Mood in Parents of Children with Sleep Disturbances - Varma P (Dove Medical Press, 2020)
Prerna Varma,1 Russell Conduit,1 Moira Junge,2 Melinda L Jackson1,3 1School of Health and Biomedical Sciences, RMIT University, Melbourne, Australia; 2Sleep Health Foundation, Blacktown, Sydney, Australia; 3Turner Institute for Brain and Mental Health, School of Psychological Sciences, Monash University, Clayton, Melbourne, AustraliaCorrespondence: Prerna Varma; Russell ConduitSchool of Health and Biomedical Sciences, RMIT University, Melbourne, AustraliaEmail prerna.varma@rmit.edu.au; russell.conduit@rmit.edu.auObjective: The current study examined sleep and mood associations in parents of children with sleep disturbances across a sample of typically developing children and children with neurodevelopmental disorders. The mediating effect of children’s sleep on the relationship between parents’ sleep and mood was also assessed. The study explored differences in parents’ sleep based on whether 1) the child had a sleep disturbance, and 2) the child was typically developing or had a neurodevelopmental disorder.Methods: A total of 293 parents of children aged 2– 12 years completed an online questionnaire. Parental sleep was examined using the Pittsburgh Sleep Quality Index, the Glasgow Sleep Effort Scale and the Pre-sleep Arousal Scale, and mood was assessed using the Profile of Mood States-short form. Measures for children included the Child’s Sleep Habits Questionnaire (CSHQ) and the Strengths and Difficulties Questionnaire.Results: Across the overall sample, children’s sleep disturbances were associated with parents’ sleep disturbances, accounting for 22% of the change in parental sleep quality. Children’s sleep partially mediated parents’ sleep and mood. Significant differences were observed for sleep and mood outcomes in parents of children with sleep disturbances (CSHQ scores ≥ 41). However, no significant differences were reported for children’s sleep disturbances and parents’ sleep quality based on whether the child was typically developing or had a neurodevelopmental disorder.Conclusion: Parents of children with sleep disturbances experience poor sleep and high pre-sleep arousal, indicative of insomnia. Given that these parents experience cognitive arousal and insomnia, it is recommended that parents’ sleep problems are addressed and treated in clinical settings.Keywords: mother’s sleep, parent sleep, children sleep, sleep quality, family